Coexistence of a Leaky SCID Phenotype With Hyperphenylalaninemia in an Adult Case - Ugur Musabak; Tuba Erdogan; Muserref Sule Akcay; Serdar Ceylaner (Case Reports in Immunology)
In recent years, due to the widespread use of advanced molecular diagnostic methods, it has become clear that individuals in particular born from consanguineous marriages may be carriers of different genetic diseases. For this reason, cases where diseases related to inborn errors of immunity (IEI) and metabolism errors are detected in the same patient are encountered more frequently. In patients affected by different genetic defects, the pathophysiology is more complex, and disease management is more difficult. In this article, we aimed to draw attention to this complex genetic carrier state in a male with primary immunodeficiency (PID). In the patient who presented with recurrent lower respiratory tract infections, bronchiectasis, asthma and nasal polyps, and antibody deficiencies as well as cellular immunodeficiency findings were detected in the immunological analyses. In the whole exome sequencing (WES) study, three different variants were detected, two in genes related to PIDs (DCLRE1C and TNFRSF13B) and one in the gene related to phenylalanine metabolism (phenylalanine hydroxylase (PAH)). In the light of the current findings, the patient was evaluated as having leaky severe combined immunodeficiency (SCID) with immune phenotype T−B−natural killer (NK)+ and hyperphenylalaninemia (HPA). This case showed us that metabolic diseases may accompany a delay in the diagnosis of SCID and patients should be evaluated with a multidisciplinary approach.